Thermally reversible photochromism of dipyrrolylethenes12. Issue 9 (6th February 2019) - Inaba, Kohei; Iwai, Ryota; Morimoto, Masakazu; Irie, Masahiro
Abstract : A robust dipyrrolylethene derivative which undergoes thermally reversible and fatigue resistant photochromic reactions with appropriate fading rates has been designed and synthesized. Abstract : Although diarylethene derivatives are considered to undergo thermally irreversible photochromic reactions, this is not always the case. Here, we report on thermally reversible photochromic diarylethenes having pyrrole-2-carbonitrile aryl groups. The thermal stability of the coloured closed-ring isomer of 1, 2-bis(2-alkyl-5-cyano-1-methyl-3-pyrrolyl)perfluorocyclopentene was found to depend on alkyl substituents at the 2- and 2′-positions. The closed-ring isomer of the ethyl-substituted derivative thermally returned back to the open-ring isomer much faster than that of the methyl-substituted derivative. The difference in the thermal stability was well explained by the ground state energy difference between open- and closed-ring isomers. Excellent fatigue resistance and appropriate thermal fading rates were observed for the derivative having cyano substituents at the 5- and 5′-positions and methyl substituents at the 2-, 2′-, 4- and 4′-positions. The UV-irradiated colouration and thermal decolouration cycle can be repeated more than 10 3 times.